Transformasi Digital dan Dampaknya terhadap Profitabilitas UMKM: Studi di Sekayu - Rafi Anggara (Yayasan Literasi Sains Indonesia, 2026)
The advancement of digital technology has significantly transformed marketing practices, particularly for Micro, Small, and Medium Enterprises (MSMEs) that must continuously adapt to evolving consumer behavior and competitive market environments. Digital marketing has emerged as an effective approach to expanding market reach, strengthening customer engagement, and supporting business profitability. This study examines the impact of digital marketing strategies on the profitability of MSMEs operating in the Sekayu region. A quantitative research design was applied using a survey method, involving 275 MSME owners as respondents. The independent variables include digital marketing strategy, digital content quality, customer interaction, and social media utilization, while profitability serves as the dependent variable. Data were analyzed using validity and reliability testing, classical assumption analysis, and multiple linear regression. The findings reveal that all digital marketing variables have a positive and significant influence on MSME profitability. The coefficient of determination (R²) of 0.674 suggests that the proposed model explains a substantial proportion of profitability variation. These results highlight the strategic importance of digital marketing optimization in enhancing MSME competitiveness and long-term sustainability.